The effect of Health Promotion Program with Collaborative Approach on Body Weight of Overweight Elementary School Girls - saeedeh jafarzadeh; sima mohamadkhan kermanshahi; Ebrahim Hajizadeh (Fasa University of Medical Sciences, 2014)
Background & Objective: Increase trend of overweight in recent years has become a concerning matter, which is a health alarm for children. Therefore, the present study investigated the impact of health promotion programs with collaborative approach on the weight of overweight school age girls. Materials & Methods: This quasi-experimental study was conducted in 2013, in which 80 overweight students in Firozabad were selected by non-randomized method and were divided into case and control groups. The data collecting tools were demographic information check list, electronic scale, and stadiometer. In the case group, health promotion programs with three stages of assessment, supportive planning, and evaluation was administered for three months. Children's weights in both groups were evaluated before and three months after intervention. The results were analyzed by SPSS software version 16. Results: Case and control groups were equal from the view point of average weight before the intervention (P>./05).While after intervention, "independent T test" showed a significant different between two groups in average weight after intervention (P<0/05). The paired T-test showed that the mean scores of weight for the case group decreased from 48/95 to 47/39 after intervention (P<0/05). However, the results showed that the mean scores of weight in the control group increased from 50/08 to 52/76 after study (P<0/05). Conclusion: Health promotion programs with collaboration of children, parents, and teachers could reduce the weight of overweight children. Therefore, it is proposed for using this program in order to prevent overweight and obesity in school age children.